Genomic aspects of age-related macular degeneration - Horie-Inoue, Kuniko; Inoue, Satoshi (Biochemical and biophysical research communications, 2014)
•AMD is a late-onset eye disease that impairs central vision among elderly populations.•Lipofuscin accumulation and drusen formation play a role in the pathogenesis of AMD.•Inflammatory and angiogenic pathways are implicated in the pathophysiology of AMD.•ARMS2/HTRA1 and CFH are major AMD susceptibility genes identified by GWAS.•Non-genetic factors such as smoking and high fat diet are implicated as risk factors. Age-related macular degeneration (AMD) is a major late-onset posterior eye disease that causes central vision to deteriorate among elderly populations. The predominant lesion of AMD is the macula, at the interface between the outer retina and the inner choroid. Recent advances in genetics have revealed that inflammatory and angiogenic pathways play critical roles in the pathophysiology of AMD. Genome-wide association studies have identified ARMS2/HTRA1 and CFH as major AMD susceptibility genes. Genetic studies for AMD will contribute to the prevention of central vision loss, the development of new treatment, and the maintenance of quality of vision for productive aging.